BUDAYA INOVASI DAN REFORMASI BIROKRASI - Asropi Asropi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
Bureaucratic reform in Indonesia has been proceeding for many years. However, persisting problems concerning bureaucracy have yet to be resolved. This snag may arise due to the lack of the creativity and innovation culture within government bureaucracy. Therefore, bureaucratic reform should be directed more to innovation culture and programs in order to enhance the governmentbureaucracy’s innovation capability.